The pied piper of Hamelin - Windust, Bretaigne, 1906-1960; Taylor, Irving, 1914-1983; Stanley, Harold; Johnson, Van, 1916-2008; National Broadcasting Company; Cinetel Films ([Los Angeles, CA] : NBC, 1957)
A very special piper arrives to the town of Hamelin, which is suffering a terrible plague of rats. Television adaptation of the famous legend. --
Originally released as a motion picture in 1957.
Cinematographer, William E. Snyder; editor, Norman A. Cerf; musical conductor, Pete King.
Van Johnson, Claude Rains, Lori Nelson, Jim Backus, Kay Starr.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2016).
Keywords: Pied Piper of Hamelin (Legendary character) -- Drama; Made-for-TV movies; Musical films; Film adaptations; Feature films; Internet videos; Streaming video